Special Issue “Advanced Materials for Gas Sensors” - Cristian E. Simion (MDPI AG, 2021)
Today’s view on gas sensors end-users is more directed toward miniaturization, low power consumption, and intelligent device integration aiming to reply to several hot issues such as high sensitivity, optimum selectivity, fast response/recovery transients, and good long time stability [...]